Value orientations and self-concepts a profile comparison of working and non-working undergraduate college students - De Gracia, Rosenda Agustin 1950- (1985)
This study looked into the differences in values orientations and self-concepts of working and non-working college students from selected schools in Metro Manila during the school year 1984-1985. Data were obtained by administering three sets of questionnaires to the respondents: a personal data questionnaire, a Likert-type Scale constructed by the researcher, and the Tennessee Self-Concept Scale. The study showed that working and non-working college students differed significantly in self-criticism score, political, economic, and moral religious values. The researcher recommends value clarification workshops geared towards personal growth and opportunities for self-discovery and self-expression of students.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Values; Self-perception.; Students -- Psychology